Refinement of a Combination Implement for Dry Seeding and Herbicide Application in Rice - ATHIRA THANKACHAN INDU THULASEEDHARAN SHIBINA K.V; Dr. Shaji James P (Guide) (Tavanur 2017 DEPARTMENT OF FARM POWER, MACHINERY AND ENERGY)
Refinement of a Combination Implement for Dry Seeding and Herbicide Application in Rice
Refinement of a Combination Implement for Dry Seeding and Herbicide Application in Rice